Porównanie koncepcji controllingu w małych i średnich przedsiębiorstwach oraz w dużych korporacjach - Sławiński, Michał (The Comparison of Management Accounting Systems at Small and Medium Enterprises and Big Corporations., 2006)
The purpose of this paper is an overview of management accounting systems implemented in small & medium enterprises and in big corporations. Subject to the analysis were the interdepend-encies between company size and a type of management accounting system, including the scope of work and job description. Strengths and weaknesses of various systems have been listed as well. It has been noticed that management accountants in big, international corporations are specialised at limited number of tasks, whereas in SME they are more universal. Recently big corporations tend to create even some management accounting departments instead of one, which are specialised at marketing & sales, production etc. An example of "production P&L", basing on variance analysis has been presented as well. Regarding strategic management accounting, the paper includes analysis of management accounting models in relation to 3 dimensions: time, importance of decisions to be made and company size. The relevance of suitable ERP-System has been underlined in the last paragraph.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1101, s. 224-232